Kształtowanie poziomu zadłużenia w zależności od powierzchni użytków rolniczych gospodarstw rolnych - Mądra, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The elaboration presents the debt level in relation to possessed cropland area used in agriculture farms. The article deals also with statistical regression model in which as a dependent variable chose the level of liabilities calculated per one hectare of cropland area. The presented research was surveyed in years 2004–2007, in Mazowsze and Podlasie region. Farms have been characterized by criterion of cropland area and were divided into six groups according to classification of PL-FADN. The regression models, estimated in elaborations showed that a variable of debt calculated per hectare of cropland area influenced on the degree of financial leverage and supply turnover in each year. It presented specific factors which had an impact on farmers investments decisions. The highest number of agriculture farms, which recorded foreign capital usage in financing structure, noticed in group of farms which noticed over 40 hectares of cropland area.